Urban Community Garden Agrodiversity and Cultural Identity in Philadelphia, Pennsylvania, U.S. Issue 3 (18th July 2016) - Pearsall, Hamil; Gachuz, Sheila; Rodriguez Sosa, Marcel; Schmook, Birgit; van der Wal, Hans; Gracia, Maria Amalia
Abstract: Considerable research has examined the social, cultural, economic, and community benefits of urban gardening. Few studies, however, have empirically assessed factors that influence urban community garden agrodiversity or its relationship to these dimensions of gardening. We conducted an interdisciplinary study of agrodiversity and cultural identity, based certain markers of identity, including how people see themselves with respect to race, ethnicity, or place of origin, in community gardens in Philadelphia, Pennsylvania. We conducted fifty‐six semistructured interviews with gardeners with different cultural identities in eight community gardens on their motivations for urban community gardening during 2014. We conducted plant inventories of the corresponding garden plots and found 104 cultivated edible and ornamental species and 28 varieties representing 34 families. We find that although gardens with culturally diverse gardeners did not have higher species richness, the cultural identity of the gardeners influenced species selection and reason for gardening. Further, the structure, design and species composition of garden plots reflected the identities of garden members. These finding have implications for the recent institutionalization of urban agriculture into city land policies in Philadelphia and other cities in North America.